2021
DOI: 10.3390/tropicalmed6010035
|View full text |Cite
|
Sign up to set email alerts
|

Two Cases of Natural Infection of Dengue-2 Virus in Bats in the Colombian Caribbean

Abstract: Dengue, a mosquito-borne zoonotic disease, is the most common vector-borne disease in tropical and subtropical areas. In this study, we aim to demonstrate biological evidence of dengue virus infection in bats. A cross-sectional study was carried out in the departments of Cordoba and Sucre, Colombia. A total of 286 bats were captured following the ethical protocols of animal experimentation. The specimens were identified and euthanized using a pharmacological treatment with atropine, acepromazine and sodium pen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…Different types of methodologies were used to capture the mammals studied. For rodents and marsupials, Sherman traps were used [ 113 ] and mist nets were used to capture bats [ 109 , 120 ]. In relation to NHP, dart immobilization [ 103 , 115 ] and manual capture [ 107 ] were used.…”
Section: Discussionmentioning
confidence: 99%
“…Different types of methodologies were used to capture the mammals studied. For rodents and marsupials, Sherman traps were used [ 113 ] and mist nets were used to capture bats [ 109 , 120 ]. In relation to NHP, dart immobilization [ 103 , 115 ] and manual capture [ 107 ] were used.…”
Section: Discussionmentioning
confidence: 99%
“…Bats are a megadiverse group of mammals only outnumbered by rodent diversity on the American continent. Molecular and serological detection of flaviviruses suggests exposure to flaviviruses in the wild [14][15][16][17][18][19]. For the most studied flavivirus in bats, dengue virus (DENV), a peridomestic study found only limited exposure of bats, likely due to proximity to humans and consumption of DENV vectors [20].…”
Section: Introductionmentioning
confidence: 99%
“…Bats have long been suspected as being a reservoir for arboviruses, including alphaviruses and flaviviruses, but their contribution to arbovirus dynamics is not known and can vary widely. Some flaviviruses such as dengue virus (DENV) and West Nile virus (WNV) have been detected in bats [22,23]. Additionally, serological evidence exists supporting exposure of bats to encephalitic alphaviruses in the field, and experimental data demonstrate the susceptibility of bats to infection with alphaviruses, including VEEV [23].…”
Section: Introductionmentioning
confidence: 99%